The Role Of Digital Accountant 5.0 Towards The Accountant Profession - Salsabila Maulidiya S.B; Adam Nurdin N; Fitriatul Rohmadani; Maria Yovita R. Pandin (Jurnal Riset dan Inovasi Manajemen, 2023)
The emergence of the era of society 5.0 is colored by the rapid world of digitalization which describes almost all areas of life including the accountant profession. This study aims to determine the development of digitalization towards society 5.0 and the efforts and challenges made by the accounting profession in facing that era. In this study using a qualitative approach method with interview techniques through online and offline to 2 Respondents of Public Accounting Firms and 2 Respondents of Tax Consultant Firms. The era of Society 5.0 requires accountants to understand technology and use it in their work. The reason is, accountants play an important role in the world of finance and business, which has a positive impact on efficiency and effectiveness. Therefore, accountant learning must be adapted to technological developments to prepare future accountants who can face the challenges of the digital era.